Juridical Analysis of Responsibility of Importers of Used Goods Prohibited from Importing to Buyers of Used Goods - Pramono, Inez Putri; Hendrawan, Daniel (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The rise in buying and selling of imported second-hand clothing is caused by the government's lack of firmness in imposing sanctions on businesses importing second-hand goods. The purpose of this research is to determine the responsibility of importers which must be followed up by the government and not harm consumers in a normative legal manner. The government should follow up on import activities of used goods which are prohibited according to law by imposing sanctions on importers, including sanctions that apply in Law No. 8 of 1999 and Law No. 7 of 2014.